Some morphosyntactic and typological tendencies in East Polissian border dialects - Del Gaudio, Salvatore (Current issues of Ukrainian linguistics: theory and practice, 2025)
In Ukrainian and, more generally, East Slavic dialectology phonetics and lexis have been more systematically studied than other language levels such as morphology, syntax and phraseology. Notwithstanding the existence of primary and secondary sources such as dialectal Atlases, academic manuals and a long series of contributions on different dialectal aspects, studies devoted to dialectal morphosyntactic and typological characteristics are very limited, if not inexistent. This applies even more to border dialects.Thus, this paper concisely outlines some morphosyntactic and typological tendencies typical of East Polissian border dialects, focusing on the area situated in the former district of Ripky (northwest of the town of Chernihiv) and extending towards Belarus. The core features of possessive constructions and the future of imperfective verbs are briefly described. Most of the reported syntactic characteristics (short sentences, ellipses, parataxis, etc.) are equally typical of spontaneous, colloquial speech and other non-standard varieties. The sample data are derived from recorded materials carried out in this specific dialect area between 2012 and 2018.Subordination, although less complex than the respective standard languages, tends to follow the Ukrainian Belarusian pattern with some overlaps that, at a first level of analysis, could be ascribed to Russian influence on Ukrainian and Belarusian local varieties. Even though possession and futurity, especially in relation to standard languages, have already been dealt with in linguistic-typological studies, most contributions largely neglect diatopic and diastratic variation. In this sense, the analysis of recently acquired dialect data compared with already available language-typological evidence can undoubtedly improve existing classifications of (East) Slavic and, more widely, European languages.
Keywords: Ukrainian language; East Polissian dialects; dialectology; language typology; East Slavic languages